2009
DOI: 10.1093/aob/mcn258
|View full text |Cite
|
Sign up to set email alerts
|

Why are orchid flowers so diverse? Reduction of evolutionary constraints by paralogues of class B floral homeotic genes

Abstract: The four DEF paralogues shaped floral diversity in orchids in a dramatic way by modularizing the floral perianth based on a complex series of sub- and neo-functionalization events. These genes may have eliminated constraints, so that different kinds of perianth organs could then evolve individually and thus often in dramatically different ways in response to selection by pollinators or by genetic drift. We therefore argue that floral diversity in orchids may be the result of an unprecedented developmental gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 38 publications
5
118
0
Order By: Relevance
“…Previously, we linked the pattern of expression of DEF-like genes, documented by analyses of wild-type and perianthmutant (peloric) orchids (Hsu and Yang, 2002;Tsai et al, 2004;Xu et al, 2006;Kim et al, 2007), with data that we had generated on the molecular phylogeny of these genes (Mondragó n-Palomino and Theißen, 2008Theißen, , 2009. We found that DEF-like genes of orchids are grouped into four wellsupported ancient clades (Figure 1b), and that genes from a specific clade are expressed in the same organs of the perianth.…”
Section: The 'Orchid Code'mentioning
confidence: 92%
See 4 more Smart Citations
“…Previously, we linked the pattern of expression of DEF-like genes, documented by analyses of wild-type and perianthmutant (peloric) orchids (Hsu and Yang, 2002;Tsai et al, 2004;Xu et al, 2006;Kim et al, 2007), with data that we had generated on the molecular phylogeny of these genes (Mondragó n-Palomino and Theißen, 2008Theißen, , 2009. We found that DEF-like genes of orchids are grouped into four wellsupported ancient clades (Figure 1b), and that genes from a specific clade are expressed in the same organs of the perianth.…”
Section: The 'Orchid Code'mentioning
confidence: 92%
“…Specifically, genes from clade 1 (PeMADS2-like genes) and clade 2 (OMADS3-like genes) are expressed in all tepals (Hsu and Yang, 2002;Tsai et al, 2004;Xu et al, 2006), whereas genes from clade 3 (PeMADS3-like genes) are only expressed in inner tepals (Tsai et al, 2004;Xu et al, 2006;Kim et al, 2007), and genes from clade 4 (PeMADS4-like genes) are exclusively expressed in the labellum (Tsai et al, 2004). This suggested a simple combinatorial model for organ identity specification that we termed the 'orchid code' (Mondragó n-Palomino and Theißen, 2008Theißen, , 2009). Assuming (e) The expression of class-B genes was also analyzed in the organs of both wild-type and peloric buds of the Phalaenopsis hybrid 'Athens'.…”
Section: The 'Orchid Code'mentioning
confidence: 99%
See 3 more Smart Citations